Metacarpal Arc Motion: Comparison of Different Measurement Methods - Büren, Carina; Al Maktary, Abdullah; Windolf, Joachim; Gehrmann, Sebastian V. (Journal of Hand and Microsurgery, 2020)
Introduction The range of motion of the carpometacarpal (CMC) joints is difficult to assess in clinical practice.Materials and Methods The purpose of this study was to measure a precise range of motion measurement of the metacarpal arc during maximum palmar flexion of the fifth CMC joint in healthy persons with three different methods: optical, electrogoniometrical, and sonographical.Results The metacarpal arc motion measured with the optical technique was 24.9 degrees (standard deviation [SD]: 6.2 degrees), with the electrogoniometric technique was 24.3 degrees (SD: 3.6 degrees) and with sonography was 25.1 degrees (SD: 3.5 degrees), with no differences between left and right hand for all methods.Conclusion This study shows that different techniques can be used for the measurement of the metacarpal arc motion. With these techniques, it is possible to assess the metacarpal arc in patients with fractures to the CMC joints to evaluate posttraumatic function und rehabilitation progress. This study shows level of evidence as III.
Keywords: metacarpal arc; carpometacarpal joints; electrogoniometer; range of motion